If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(5x+3)=-6-+12
We move all terms to the left:
-2(5x+3)-(-6-+12)=0
We add all the numbers together, and all the variables
-2(5x+3)-0=0
We add all the numbers together, and all the variables
-2(5x+3)=0
We multiply parentheses
-10x-6=0
We move all terms containing x to the left, all other terms to the right
-10x=6
x=6/-10
x=-3/5
| 4t-19=16-t | | -2(5x+3=-6-+12 | | 3p/2=-12 | | 105=7(x+7) | | 3x-2(2+3)=4x-100 | | -2x-10=2x+26 | | 6x+14=446x= | | -20k+20=-18k+5-15 | | 3(x2)-24x=0 | | -x-2/4=3x+6/2 | | -14-x=-70 | | x-8=16+4x | | 4t^2-11=2 | | 30=9-3u | | -552=-8(5-8r) | | -6u-1=-9u+4u-2 | | 292=177-v | | 1-0.75(v+2)=-5 | | 2p/3=8 | | 4x2-36=0 | | 2p/5=8 | | 300=(3)(9.8)(h) | | 33m=21 | | -7(4-4x)=84 | | 10-4d=-5-9d | | 4/3(7-n)=13 | | x-7=11+4x= | | 9y+10=7y | | (7x+4)=4x-6(2-x)+7 | | 108=2x-4 | | -7x+6=-71/6 | | 17.3=x-3.3 |